Correlates of diabetic polyneuropathy of the elderly in Sub-Saharan Africa. - Nadine Simo; Callixte Kuate-Tegueu; Steve Ngankou-Tchankeu; Jacques Doumbe; Youssoufa Maiga; Matteo Cesari; Jean-François Dartigues; Andre-Pascal Kengne; Maturin Tabue-Teguo (PLoS ONE, 2020)
Background Diabetic polyneuropathy is associated with significant physical disability among older adults. However, their frequency and correlates are not well known in the older adults in Sub-Saharan-Africa. The objectives were to evaluate the hospital-based prevalence of diabetic polyneuropathy and identify its correlates in older adults. Methods Over a period of 5 months, a cross-sectional survey was carried out at Douala Laquintinie Hospital (DLH), a main reference hospital in Douala, the economic capital of Cameroon. Participants in our study group comprised all patients with type 2 diabetes, whatever the reason for their reporting to the hospital. Diabetic Polyneuropathy was defined according to a Diabetic Neuropathy Examination score > 3/16. Results A total of 159 older adults with diabetes were examined during this recruitment period, among whom 106 (66.7%) were women. The mean age was 68.3 ± 6.5 years. Diabetes median duration was 108 months. For all patients assessed using the Diabetic Neuropathy Examination score, polyneuropathy was reported in 31.4%; among them, polyneuropathy proved symptomatic in 78% of them. Correlates of polyneuropathy were glycated hemoglobin (p = 0.049), HIV infection (p = 0.031) and albuminuria (p< 0.001), even after adjustment for age, gender and duration of diabetes. Conclusion A third of older adults with diabetes who visited our hospital were diagnosed with prevalent diabetes-related polyneuropathy. It shows that early detection is required through routine screening and regular follow-up examinations in order to reduce the risk of disability and improve the quality of life in elderly diabetics.